SATELLITE-BASED TOLL COLLECTION SYSTEMS: ENHANCING EFFICIENCY AND SUSTAINABILITY IN MODERN TRANSPORTATION NETWORKS - Venkateswarlu Mullangi (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article comprehensively analyzes GPS-based toll collection systems as a transformative solution for modern transportation infrastructure. The article examines the evolution from traditional toll collection methods to sophisticated satellite-based systems, highlighting technological advancements, implementation methodologies, and real-world applications. The article demonstrates significant improvements in operational efficiency, environmental sustainability, and economic viability through extensive analysis of case studies across multiple countries. The article encompasses system architecture, including On-Board Units, Wireless Sensor Networks, and cloud platforms, while addressing critical aspects of data security and user privacy. The article reveals substantial benefits regarding reduced traffic congestion, enhanced revenue collection, decreased environmental impact, and improved user experience, supported by evidence from successful implementations in various global contexts.